2016
DOI: 10.1094/phyto-11-15-0285-r
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Structure, Virulence, and Fungicide Sensitivity of Fusarium fujikuroi in Taiwan

Abstract: The rice disease bakanae, caused by Fusarium fujikuroi Nirenberg, has been present in Taiwan for over a century. To better understand the genetic diversity and structure of F. fujikuroi, a set of 16 polymorphic simple sequence repeat (SSR) markers were newly developed and used to analyze 637 F. fujikuroi isolates collected in 14 cities or counties around Taiwan from 1996 to 2013. On the basis of Bayesian clustering, the isolates were classified into four highly differentiated clusters: cluster B likely derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…Fusarium fujikuroi genetic structure is mainly clonal in Italy, but the 1:1 ratio of mating type alleles found in 6 out of 8 Italian fungal populations indicates that sexualreproduction of F. fujikuroi may occur in the field (29). Similar coexistence of both mating types was also observed within F. fujikuroi populations in Taiwan (7).…”
Section: Pathogenicity and Monitoring Of Fusarium Fujikuroimentioning
confidence: 64%
See 2 more Smart Citations
“…Fusarium fujikuroi genetic structure is mainly clonal in Italy, but the 1:1 ratio of mating type alleles found in 6 out of 8 Italian fungal populations indicates that sexualreproduction of F. fujikuroi may occur in the field (29). Similar coexistence of both mating types was also observed within F. fujikuroi populations in Taiwan (7).…”
Section: Pathogenicity and Monitoring Of Fusarium Fujikuroimentioning
confidence: 64%
“…To this end, molecular techniques were initially developed using random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP) techniques, and electrophoretic karyotype analysis to separate Fusarium isolates with different degrees of virulence, and to distinguish among the different species of GFSC (32,33). Recently, a set of various polymorphic simple sequence repeat (SSR) marker have been developed as a sensitive molecular technique for characterization of the genetic variation among different F. fujikuroi populations (7,29).…”
Section: Molecular Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of TR 34 /L98H/S297T/F495I isolates in Taiwan might be attributed to widespread use of prochloraz over the past 3 decades. Studies have suggested an association between use of imidazole fungicides and emergence of azole-resistant A. fumigatus with TR 34 / L98H/S297T/F495I mutations (7,8).…”
Section: Multicenter Study Of Azole-resistant Aspergillus Fumigatus Cmentioning
confidence: 99%
“…In various rice growing countries, significant yield losses caused by the disease can range from 50% to more than 70% (Ou 1985; Rood 2004). Increasing bakanae disease incidence has been reported in Italy (Amatulli et al 2012) and major growing areas of Asia such as Pakistan, South Korea, Bangladesh, Northern India, and Taiwan (Khan et al 2000; Park et al 2009; Haq et al 2011; Gupta et al 2014; Chen et al 2016). …”
Section: Introductionmentioning
confidence: 99%